Reduced intensity stem cell transplantation for advanced soft tissue sarcomas in adults: a retrospective analysis of the European Group for Blood and Marrow Transplantation - Simona Secondino; Matteo G. Carrabba; Paolo Pedrazzoli; Luca Castagna; Francesco Spina; Federica Grosso; Alexia Bertuzzi; Jacques-Olivier Bay; Salvatore Siena; Paolo Corradini; Dietger Niederwieser; Taner Demirer (Haematologica, 2007)
We conducted a retrospective analysis on adult patients with advanced soft tissue sarcoma (STS) other than rhabdomyosarcoma who received allogeneic stem cell transplantation and were registered at the EBMT database. The aim of of the study was to assess whether an immune-mediated graft-versus-tumor (GVT) effect could be generated in this disease. Among 26 patients included in the registry, 14 were eligible for this analysis as they had received reduced intensity stem cell transplantation for chemorefractory disease. Two patients died of transplant-related complications and eight of progressive disease; four are alive and experienced long-lasting disease stabilisation following transplant. Our study may suggest that an immune-mediated effect cannot be excluded in some STS.